Percepción de alimentación saludable y conductas alimentarias en los estudiantes de las Unidades Educativas del Cantón Olmedo - Ordóñez Riofrio, María Soledad (2024)
The perception of healthy eating is the process acquired by people on the consumption of food considered adequate for health and is directly linked to the experiences, food, senses, tastes, food preparations according to the context where they live; That is why today it has become a health problem of great impact on young people, since having an inadequate diet can generate a decrease in the response of the immune system, as well as alter the physical and mental development, compromised growth and unhealthy eating behaviors, which in turn generate overweight, obesity, dyslipidemia, eating disorders, affecting more frequently adolescents. The present study aimed to determine the perception of healthy eating and eating behaviors in students of the Educational Units of Olmedo Canton, during the period October 2022 - March 2023. A descriptive study with a cross-sectional quantitative approach was conducted. Two surveys were applied, on perception of healthy eating; and a questionnaire of attitudes towards food, in which 365 students participated. The following results were obtained. 84.38% of the students have an adequate perception of healthy eating, followed by 13.43% with a regular perception and 2.19% with a perception of inadequate eating. Regarding eating behaviors, 82.74% of the students are not at risk of eating disorders and 17.26% are at risk of eating disorders. Through the statistical analysis of chisquare test it was observed that there is a statistically significant relationship between the level of perception of healthy eating and eating behaviors, thus concluding that most students have an adequate perception of healthy eating and no risk of eating disorders